Comparing Video Media and Teaching Aids to Improve Maternal Knowledge of the ‘Fill My Plate' Nutrition Program: A Quasi-Experimental Study in Indonesia - Urhuhe Dena Siburian; Paruhum Ritonga (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Stunting remains a significant public health challenge in Indonesia, affecting an estimated 30% of children as of 2023. One of its primary causes is inadequate dietary intake. In response, the Indonesian government introduced the Fill My Plate nutrition program, promoting food diversity and appropriate portion sizes to ensure balanced meals. This study aimed to compare the effectiveness of video media and teaching aids in improving maternal knowledge of the Fill My Plate program as a strategy to prevent stunting. A quasi-experimental design with pre-test and post-test groups was utilized. The study was conducted in North Tapanuli Regency from July to December 2024, involving 30 mothers of toddlers. Participants were randomly assigned to either the video media group (n = 15) or the teaching aids group (n = 15). Maternal knowledge was assessed using a structured and validated questionnaire. Descriptive statistics were applied for univariate analysis, and an Independent Sample t-test was used for bivariate analysis at a 95% confidence level (α = 0.05). Mean differences were calculated to determine effect sizes. The results both interventions significantly improved maternal knowledge (p < 0.05). However, there was no statistically significant difference between the two groups (p > 0.05), indicating that video media and teaching aids were equally effective as educational tools. No statistically significant difference was observed between the two groups (p = 0.710). Video media and teaching aids are both effective in enhancing maternal knowledge about the Fill My Plate nutrition concept. Health educators are encouraged to integrate these media formats into community-based health programs to strengthen maternal engagement and support stunting prevention efforts Keywords: Fill My Plate, Maternal knowledge, Nutrition, Teaching aids, Video media